2019
DOI: 10.1007/s00403-019-02009-5
|View full text |Cite
|
Sign up to set email alerts
|

5-0 Polypropylene versus 5-0 fast absorbing plain gut for cutaneous wound closure: a randomized evaluator blind trial

Abstract: Background: Surgeons have mixed opinions regarding cosmetic outcomes of 5-0 fast absorbing plain (FG) gut relative to nonabsorbable suture material, such as 5-0 polypropylene (PP). High quality randomized trials comparing these two suture materials are lacking.Objectives: To determine whether the use of PP during layered repair of linear cutaneous surgery wounds improves scar cosmesis compared to wound closure with FG.Methods: A randomized, split wound, comparative effectiveness trial was undertaken. Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 21 publications
(17 reference statements)
0
13
0
Order By: Relevance
“…By contrast, a randomized blind‐evaluator trial ( n = 44) suggested that overall patient opinion favoured nonabsorbable sutures 7 . This study compared absorbable (fast‐absorbing plain gut) with nonabsorbable (polypropylene) sutures.…”
Section: Rapidly Absorbable Vs Nonabsorbable Suturesmentioning
confidence: 93%
See 1 more Smart Citation
“…By contrast, a randomized blind‐evaluator trial ( n = 44) suggested that overall patient opinion favoured nonabsorbable sutures 7 . This study compared absorbable (fast‐absorbing plain gut) with nonabsorbable (polypropylene) sutures.…”
Section: Rapidly Absorbable Vs Nonabsorbable Suturesmentioning
confidence: 93%
“…By contrast, a randomized blind-evaluator trial (n = 44) suggested that overall patient opinion favoured nonabsorbable sutures. 7 This study compared absorbable (fast-absorbing plain gut) with nonabsorbable (polypropylene) sutures. A small but statistically significant better cosmetic outcome was reported with nonabsorbable sutures (P < 0.001).…”
Section: Rapidly Absorbable Vs Nonabsorbable Suturesmentioning
confidence: 99%
“…The power analysis tested the alternative hypothesis that, compared with 2‐cm subcuticular suture, 1‐cm subcuticular suture would result in a better cosmetic outcome, as measured by the primary outcome. A priori power analysis assumptions were a minimal meaningful clinical difference of 3 points on the 60‐point POSAS scale, 90% power, an alpha level of 0·05 and SD of 6, as seen with previous studies performed by the authors 1–3,5 . Using a paired t ‐test with two tails and expecting an attrition rate of 20%, it was determined that we needed to enrol 50 patients.…”
Section: Methodsmentioning
confidence: 99%
“…Prior studies have compared the use of various wound closure methods and materials, yet there are no studies comparing the aesthetic outcome of subcuticular suture spacing. [1][2][3][4][5][6][7][8][9][10] The goal of this study was to determine whether wound halves closed with 1-cm spaced subcuticular sutures would result in better cosmetic outcomes than halves closed with 2-cm spaced subcuticular sutures. Given the lack of prior studies or standards on subcuticular suture spacing, the 1-cm vs. 2-cm interval was chosen based on the senior author's perception of the common range of subcuticular suturing distances observed during his clinical practice over the past 19 years.…”
Section: What Does This Study Add?mentioning
confidence: 99%
See 1 more Smart Citation